2016
DOI: 10.4236/ijmpcero.2016.51011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cut-Off Frequency of Butterworth Filter on Detectability and Contrast of Hot and Cold Regions in Tc-99m SPECT

Abstract: In SPECT, noise is one of the major limitations that degrade image quality. To suppress the noisy signals in an image, digital filters are most commonly applied. However, in SPECT image reconstruction, selection of an appropriate filter and its functions has always remained a difficult task. In this work an attempt was made to investigate the effects of varying cut-off frequencies and in keeping the order of Butterworth filter constant on detectability and contrast of hot and cold regions images. A new insert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Specimen areas were selected, and individual images were saved in a 24-bit RGB TIFF file format with a resolution of 1 μm/pixel using the ZEISS Microscopy Software. The slides with periostin staining were used for quantitative analysis using ImageJ ( https://imagej.net/ij/ ) 59 . The images were converted 8-bit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimen areas were selected, and individual images were saved in a 24-bit RGB TIFF file format with a resolution of 1 μm/pixel using the ZEISS Microscopy Software. The slides with periostin staining were used for quantitative analysis using ImageJ ( https://imagej.net/ij/ ) 59 . The images were converted 8-bit.…”
Section: Methodsmentioning
confidence: 99%
“…Specimen areas were selected, and individual images were saved in a 24-bit RGB TIFF file format with a resolution of 1 μm/pixel using the ZEISS Microscopy Software. The width of the gap between the opposing edges was measured at four arbitrary points at each time point using ImageJ software ( https://imagej.net/ij/ ) 59 . The means across all four measurements were calculated, normalized to the time 0-h, and compared between the CM CTL and CM POSTNhigh using two-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it also indicated that the impact on image quality varies with respect to the size of hot regions as well as the count density in the region of interest which is the case in this study. Moreover, higher frequency corresponds to small regions and to abrupt changes in the count density of regions of interest [26][27][28][29].…”
Section: International Journal Of Biomedical Imagingmentioning
confidence: 99%
“…Noise removal of raw SPECT projection data has been typically conducted by a low-pass filter to eliminate high-frequency noise which causes artifacts of SPECT reconstruction [2] [3] [4] [5] [6]. A Butterworth filter, which is usually used as a low-pass filter, however, cannot distinguish signal from noise.…”
Section: Introductionmentioning
confidence: 99%